A case of a patient with severe renal failure on hemodialysis treated with vismodegib for relapsing basal cell carcinoma. Issue 6 (December 2018) - Sbrana, Andrea; Antonuzzo, Andrea; Galli, Luca; Biasco, Elisa; Musettini, Gianna; Paolieri, Federico; Ricci, Sergio
Introduction: Basal cell carcinoma (BCC) is the most common skin cancer. Treatment options for metastatic or locally advanced BCC inappropriate for surgery or radiotherapy were poor until vismodegib was approved for use in this setting. This drug can be safely used in patients with mild to moderate renal impairment, but limited data are available for its use in case of severe kidney failure. We present the case of a patient with severe renal failure on hemodialysis treated with vismodegib. Case description: An 83-year-old patient with relapsing BCC of both auricles and severe renal failure on hemodialysis was treated with vismodegib for 7 months. The treatment proved to be effective with a striking reduction of the tumor masses. The patient was on therapy with vismodegib for 7 months and no severe adverse event was observed. Conclusion: Vismodegib could be used in patients with severe renal impairment, but these patients must be attentively followed and strict cooperation among healthcare professionals, such as nephrologists, dermatologists, and medical oncologists, is required.